Vision sur L'activité Bancaire Islamique en Algérie à la Lumière du Règlement 20/02 - Nasri, Nasreddine; Ayadi, Abdelkader (جامعة حسيبة بن بو علي بالشلف - مخبر العولمة واقتصاديات شمال إفريقيا, 2021)
This study is concerned with the reality of Islamic banking in Algeria and its legislative framework, by analysing the legislative texts issued recently by the Bank of Algeria, and reviewing the Algerian banking system and the most important stages of its development. Then, it attempts to present a vision for the future of this sector in light of recent regulations, especially the 02/20 system. The study concluded that the Islamic banking sector in Algeria is still in the take-off stage, and that the legal framework is ready; it is for banks, now, to interact positively and develop Islamic banking operations, which are currently limited to some banks only. As for Islamic finance in general in Algeria, the authorities must continue to build the necessary legal framework and involve all other actors, especially the securities market.
Keywords: المصارف الإسلامية -- النظام المصرفي -- الاقتصاد الجزائري